2014
DOI: 10.1021/ma402497y
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Spaced Concentric Vesicles and Polymerizations in RAFT Dispersion Polymerization

Abstract: Different from concentric vesicles without spacing between the walls, the concentric vesicles with uniform spacing between the walls were rarely fabricated. We successfully fabricate the spaced concentric vesicles (SCVs) via RAFT dispersion polymerization, and continuous propagation of the residual polymer chains inside the large vesicles induces self-assembling to form SCVs. Concentration of the residual polymer chains in the solution of the nascent-formed vesicles is the determining factor for formation of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 34 publications
2
95
0
Order By: Relevance
“…The former component was subsequently stabilized by the P4VP-PS diblock copolymer chains, resulting in the formation of PS spherical nanoparticles within the vesicle lumen and hence the 'yolk/shell' morphology. More recently, Zhang et al [57] reported the formation of 'multi-shelled' vesicles when targeting highly asymmetric (e.g. P4VP 73 -PS 9400 ) diblock copolymers in methanol (Figure 4e).…”
Section: 1dispersion Polymerization Of Styrenementioning
confidence: 99%
See 3 more Smart Citations
“…The former component was subsequently stabilized by the P4VP-PS diblock copolymer chains, resulting in the formation of PS spherical nanoparticles within the vesicle lumen and hence the 'yolk/shell' morphology. More recently, Zhang et al [57] reported the formation of 'multi-shelled' vesicles when targeting highly asymmetric (e.g. P4VP 73 -PS 9400 ) diblock copolymers in methanol (Figure 4e).…”
Section: 1dispersion Polymerization Of Styrenementioning
confidence: 99%
“…Pan and co-workers [28,[52][53][54][55][56][57] have utilized a trithiocarbonate-based chain transfer agent (DDMAT, see Figure 2a) to prepare a range of poly(4-vinylpyridine) (P4VP) macro-CTAs for the subsequent dispersion polymerization of styrene in methanol. The resulting poly(4-vinylpyridine)-polystyrene (P4VP-PS) nanoparticles formed a wide range of copolymer morphologies ( Figure 3 andFigure 4) [28,[52][53][54][55][56][57].…”
Section: 1dispersion Polymerization Of Styrenementioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14] However, fabrication of polymeric nanoparticles is usually a tedious and time-consuming process, which is often uneconomic and difficult to scale up. [15][16][17][18] Direct fabrication of nano-objects via polymerizationinduced self-assembly (PISA), which have been developed in recent years, [19][20][21][22][23][24][25][26] may be one of the best methods to solve this problem. PISA strategy allows fabricating of polymeric nanoparticles at much high concentrations, and has become a powerful strategy for fabrication of polymeric nanoparticles.…”
Section: Introductionmentioning
confidence: 99%